Monetary policy and the stock market: Insights from a model of endogenous business cycles - Boyan Yanovski (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2016)
[Key Takeaways] * Monetary policy might be ineffective in its attempt to influence the borrowing conditions over the business cycle because of the existence of adverse endogenous factors (like an endogenous risk premium, for example) counteracting monetary policy. * The evolution of the stock market over the business cycle can be considered an indicator of the extent to which monetary policy is able to affect the current borrowing conditions in the economy. * The pro-cyclical stock market observed in the US during the last 25 years in the presence of a counter-cyclical monetary policy can be considered evidence of monetary policy ineffectiveness and/or weak reactivity. * Monetary policy might be ineffective in reducing endogenous business cycle fluctuations because of the lags involved in its reactions and in the transmission process.
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: 330